Letter - Halifax, Edward Frederick Lindley Wood, Earl of, 1881-1959
026-0008-001 Foreign Office, S.W.1. 25th August, 1939. Dear Sir Walter, I am now able to reply to your letter WMC/WJB/MS/1,388 which I received on the 22nd August, regarding the desire of Señor Pascual Tomas to send some money to his wife and daughters in Valencia and am glad to let you know that, as an exceptional measure, we are prepared to have the money transmitted through our Consul there. If, therefore, you will be good enough to send me a sterling cheque, made payable to the Finance Officer, Foreign Office, we will then instruct the Consul to give Señor Pascual's wife the equivalent in pesetas. For reasons which you will appreciate the less said about this transaction the better for Señora Tomas and all concerned. Yours sincerely, Halifax Sir Walter Citrine, K.B.E. 292/946/26/8